Brainwashing for beginners : a critical analysis of the discursive construction of the Covid-19 vaccine debate on the Stellenbosch University Facebook page from 2020-2022 - Bronn, Chelsea (2022)
Thesis (MA)--Stellenbosch University, 2022.